Model of financing regional development - Polish versus Western European regions - Aleksandra Poproch; Janusz Zaleski; Zbigniew Mogiła (European Regional Science Association (ERSA), 2013)
The Policy of regional development consists of two crucial components: objectives and the system of their achieving. Financial resources comprise one of the main parts of the latter. The aim of the paper is to present the system of financing the socio-economic regional development in Poland after its accession to the European Union in 2004 which has opened up an opportunity to significantly augment development funds for the Polish regions - primarily through the Cohesion Policy. It must be emphasized that Poland has become the largest national beneficiary of EU Cohesion Policy expenditure in the financial perspective 2007-2013 and it is expected to be the leader in this regard within the new EU Financial Framework 2014-2020.This has created a great opportunity for the Polish regions to accelerate and improve the long-term quality of their socio-economic development. In this paper we concentrate on the two different regions. The first one is Dolnosl±skie - a representative of the group of relatively affluent regions (112.5% of GDP per capita of the national average; 66% of GDP per capita in PPS of the EU average), characterised by high investment attractiveness, large human and social capital stocks as well as other endogenous potentials that predestine this region to be one of the leaders of socio-economic development in Poland. The other region in question is Podlaskie - a voivodeship that belongs to the group of regions marked by a relatively low level of development as approximated by GDP per capita (72.7% of the national average; 45%of GDP per capita in PPS of the EU average) and which is included in the problem NUTS-2 regions in Poland covered by a special support programme under cohesion policy. The paper includes the analysis of historical data and presents the forecasting method of financial resources allocated for regional development. Subsequently, the forecasts are presented with special emphasis upon own resources of the regions, central budget funding, UE funds as well as private investment including foreign direct one. The main conclusions and insights are contrasted with the results of desk research on selected Western European regions enabling to address the question of long-term efficiency of different models of financing regional development.
Keywords: R58; 330; financial resources; regional development; Cohesion Policy